2012
DOI: 10.1088/0967-3334/33/5/739
|View full text |Cite
|
Sign up to set email alerts
|

Level-set-based reconstruction algorithm for EIT lung images: first clinical results

Abstract: We show that electrical impedance tomography (EIT) image reconstruction algorithms based on the Level Set (LS) method are suitable for real data, which is breathing data in our application. The LS based reconstruction method (LSRM) helps track fast topologically changing interfaces, which are typically smoothed by traditional voxel based reconstruction method (VBRM), during the monitoring process. We represent lung images by applying the LSRM using difference solver and then compare the results with the VBRM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…To represent a two-dimensional closed interface, one can use the geometric nodes method [11] or the level sets method [14]. Here, we assume the deposit interface is smooth and star-shaped.…”
Section: (B) Permittivity and Interface Representationmentioning
confidence: 99%
“…To represent a two-dimensional closed interface, one can use the geometric nodes method [11] or the level sets method [14]. Here, we assume the deposit interface is smooth and star-shaped.…”
Section: (B) Permittivity and Interface Representationmentioning
confidence: 99%
“…Meantime, level set method has become powerful and versatile tool for image processing and computational physics (Vese and Chan, 2002;Fedkiw, 2001, 2003;Chung et al, 2005), also it has found applications in shape reconstruction and inverse scattering (Dorn et al, 2000;Dorn and Lesselier, 2006). More recently, applications of level set method to electrical tomography (ET) problems have been proposed (Ito et al, 2001;Soleimani et al, 2006a,b;Rahmati et al, 2012;Rahmati and Adler, 2013). In Ito et al (2001), using values of Neumann data as well as values of solution in a thin layer along the domain, level set method together with steepest descent method has been employed to solve the inverse conductivity problem.…”
Section: Introductionmentioning
confidence: 99%
“…[35], or the D-Bar method (e.g. [36]) were not evaluated, as they have seen little evaluation for thoracic EIT data (but see [37], [38]. However, we make the data and software publicly available to allow extending the comparison to a wider range of present and future algorithms.…”
Section: Introductionmentioning
confidence: 99%